Interplay Between Cybernetics and Philosophy as an Essential Condition for Learning - Maria Jakubik (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
In the 21st century, there is an increasing interest in studying the relationship of cybernetics and philosophy. My paper is also inspired by the recent enormous efforts in developing machine intelligence and machine learning to replicate human intelligence and human learning. Furthermore, my paper is motivated by the continuing merge of natural sciences and social sciences. I argue that in the network and wisdom economy, the subject of study in natural and social sciences is converging, which makes the topic of my paper interesting, contemporary, and needed. Here, I will focus on the interplay between philosophy and cybernetics as a necessary condition for learning. This conceptual paper is based on the study of the literature. After presenting the objective of the paper, I will discuss the concept of learning. Then, I present the main characteristics of the five leading learning paradigms such as behaviorism; cognitivism; cognitive and social constructivism; humanism; and connectivism. Next, I briefly discuss how cybernetics and philosophy relate to learning and offer a framework to show the interrelatedness of cybernetics, philosophy, and the learning paradigms. Finally, I conclude with my key arguments.